Draft Annual Plan 1980-81 Volume II Government of Bihar - Planning Commission (Planning Commission, 1979)
Major and Medium Irrigation Mineral Development Roads and Bridges Civil Aviation Tourism and Pilgrim Development Sewerage and Water Supply Information and Publicity Planning Machinery District Reorganization Buildings Autonomous Development Authorities
Government of Bihar
Government of Bihar Planning Department
Keywords: Introduction Financial Resources; The Plan in Outline Sub – Plan; Special Component Han; Agriculture Education and Research; Crop Husbandry; Soil and Water Conservation; Food for Work; Animal Husbandry; Investment in Agricultural Financial Institutions; Storage and Warehousing